KONSTRUKSI REALITAS TV TALKSHOW ATAS WACANA BENCI PRODUK LUAR NEGERI: ANALISIS SEMIOTIKA SOSIAL ROSI KOMPAS TV EPISODE “JOKOWI: MIRAS BATAL, BENCI PRODUK ASING!” - Endah Setyorini (Jurusan Ilmu Komunikasi Universitas Andalas, 2021)
This article discusses how Rosi, a famous television talkshow in Indonesia, constructs the reality of the “hate foreign products” discourse raised by President Jokowi in the 2021 Ministry of Trade National Working Meeting. With qualitative research methods using social semiotics analysis techniques, the study will see how the three elements of social semiotics in the MAK Halliday model (field of discourse, tenor of discourse, and mode of discourse) construct the reality of the discourse. As a result, the reality constructed can be interpreted as a form of government protection for domestic products, inability to encourage domestic products to compete with foreign products, affirmative action by the president to his people, or it could be a form of inconsistency or contradiction in the president's attitude, where the meaning can depend on the background and social processes of each individual as explained by Berger in the theory of social construction.